Respostas

A melhor resposta!
2013-12-10T21:52:45-02:00
X+y+z=1
x+3y+az=-3
x+ay+3z=2

1   1   1 : 100 
1   3   1 : 010 = L2-> - 1
1   1   3 : 001 = L3-> -1

1   1   1 : 1  0   0  = L1->L1 -1/2L2
0   2   0 : -1  0 -1 
0   0   2 : 0  0   1 

1   0   1 : -1/2  0   -1/2 
0   2   0 : -1  0 -1         = L2->L2-1
0   0   2 : 0  0   1 

 1   0    1 :   -1/2  0   -1/2       =L1->L1-1/2L3
-1   1   -1 :   -2    -1   -2         
 0   0    2 :    0     0    1 

1   0    0 :   -1/2  0   -1       
-1   1   -1 :   -2    -1   -2 =L2->L2 + L1       
 0   0    2 :    0     0    1 

1   0    0 :   -1/2  0   -1       
0   1    0 :   -5/2    -1   -3       
0   0    2 :    0     0    1 = L3->L3-1/2L3

1   0    0 :   -1/2   0   -1       
0   1    0 :   -5/2   -1  -3       
0   0    1 :   0       0   1/2 

   -1/2   0   -1       
   -5/2   -1  -3       
   0       0   1/2 
                                             
                                                         
1 5 1